Exploring the economic and environmental benefits of Colombo wetlands in urban planning with nature-based solutions - Chethika Gunasiri Wadumestrige Dona; Geetha Mohan; Kensuke Fukushi; Nadeera Dissanayaka (Societal Impacts)
Floods have become a significant economic and social issue in many cities around the world. Urban wetlands have garnered considerable attention as a nature-based solution (NbS) for urban flood control. However, due to rapid urbanization and the lack of economic recognition of wetlands' flood management functions, their role as an NbS is often undermined by unsustainable urban planning. This study evaluates the role of the Colombo Wetland Complex (CWC) in Sri Lanka as a nature-based solution for managing stormwater in the Colombo Metropolitan Area, and the impact of urbanization on this function. Between 2001 and 2024, the CWC complex has seen a reduction in the average annual area of 0.12 km²/year. Additionally, the unit value of the CWC for flood control purposes is approximately USD 72.08 per square meter. The findings of this study provide crucial insights for a wide range of stakeholders, including urban planners, hydrologists, engineers, decision-makers, environmentalists, and the public. These insights emphasize the economic, ecological, and social benefits of integrating the CWC into urban planning agendas and flood management plans as an NbS, compared to traditional flood intervention methods.